EKSPLORASI PENGALAMAN MAHASISWA DALAM MENINGKATKAN SELF CONFIDENCE MELALUI KETERLIBATAN DALAM HIMPUNAN MAHASISWA PROGRAM STUDI FAKULTAS ILMU SOSIAL DAN HUKUM UNIVERSITAS NEGERI MAKASSAR - Nur Aisya; Dalilul Falihin; Rusdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to: 1) describe the nature of student engagement in the Student Association of the Study Program, 2) identify factors that support and hinder student engagement in the Student Association of the Study Program, 3) describe the increase in students’ self-confidence through their engagement in the Student Association of the Study Program. Data were collected through observation, in-depth interviews with HMPS executives, members, and former members as informants, and documentation of organizational activities. Data were analyzed through data reduction, data presentation, and the drawing of conclusions and verification.